Deep vein thrombosis in mice is regulated by platelet HMGB1 through release of neutrophil-extracellular traps and DNA - Dyer, Mitchell R. (Sci Rep, 2018)
Venous thromboembolic (VTE) disease, consisting of deep venous thrombosis (DVT) and pulmonary embolism (PE) is a leading cause of morbidity and mortality. Current prophylactic measures are insufficient to prevent all occurrence in part due to an incomplete understanding of the underlying pathophysiology. Mounting evidence describes interplay between activation of the innate immune system and thrombus development. Recent work has demonstrated that platelet release of HMGB1 leads to increased microvascular complications following injury. Additionally, platelet HMGB1 was found to enhance DVT and increase the formation of neutrophil extracellular traps (NETs), although the role of HMGB1 induced NET release in thrombosis remains unexplored. Utilizing a transgenic mouse lacking HMGB1 specifically from platelets and megakaryocytes we now demonstrate the specific role of platelet-derived HMGB1 in acute and subacute/chronic venous thrombosis. Platelets account for the majority of circulating HMGB1 and HMGB1 deposition within the developing clot. The pro-thrombotic effect of platelet-derived HMGB1 is mediated through enhanced neutrophil recruitment, NET formation and specifically release of extracellular DNA during NET formation. Taken together, these data suggest that platelet HMGB1 mediated NET release is a primary regulator of DVT formation in mice.